Improving Student Learning Result Using Slide Media And Animated Media In Class X Geography Material SMA Negeri 2 Bantaeng - Angreny, Kiky; Edy, Hasriyanti; Zhiddiq, Sulaiman (UNM Geographic Journal, 2018)
This study aims: To determine differences in learning outcomes of students of class X by using media power point To determine the differences in the results of class X student using animation media. This type of research used in this research that the type of research experiments. The subjects of this study consisted of an experiment I, using media power point and experimental group II were using media animation using animasi.Populasi media in this study were all students of class X SMA Negeri 2 Bantaeng. Sampling with purposive sampling technique, so the sample is X.is.1 class and X.is.2 SMAN 2 Bantaengdengan consideration the average value of report cards are not much different for subjects geografi.Instrumen research use tests and assignments, while analysis Data processed by using the t test. The results showed that : Results of study on X.is.1 class based on learning outcomes obtained 28.40 .While X.is.2 33,80. tcount>ttable)(t=5,22and table = 7.42)Dari these data it can be concluded that the use of media is more animated films increased compared to the use of media slides ( power point ).